Perspektif Qur'anic Perspectives on Digital Health Ethics and Artificial Intelligence - Miftah Ulya; Nurliana, Nurliana (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
The digital revolution in global health presents great opportunities and challenges through the integration of artificial intelligence (AI), big data and telemedicine. However, the absence of a transcendent ethical foundation in the development of medical technology risks undermining human values and justice. This study aims to critically examine the direction of digital health development by integrating the ethical and spiritual values of the Qur'an. The method used is a critical qualitative approach based on library research, with normative analysis of verses related to health principles, information ethics, and maqāṣid al-syarī'ah. The results of the study show that in QS. Al-Isrā': 70 emphasizes human dignity as the basis for medical data protection; likewise in QS. Al-Syu'arā': 80 emphasizes that healing is divine and should not be separated from spiritual values; while in QS. Al-Baqarah: 286 provides guidance on the limits of responsibility and human capabilities in the utilization of technology. The critical discussion underlines the importance of building Qur'anic-based digital ethics that emphasize justice ('adālah), trustworthiness, and compassion (raḥmah) in designing equitable and inclusive artificial intelligence (AI) systems and remote health services. It is hoped that this study will provide recommendations for the development of Qur'anic Digital Ethics as a future normative framework for global digital health innovation.